Safety Assessment of Ultrasound-Assisted Intravesical Chemotherapy in Normal Dogs: A Pilot Study - Sasaki, Noboru; Ikenaka, Yoshinori; Aoshima, Keisuke; Aoyagi, Teiichiro; Kudo, Nobuki; Nakamura, Kensuke; Takiguchi, Mitsuyoshi (Frontiers in Pharmacology, 2022)
Intravesical chemotherapy after transurethral resection is a treatment option in patients with non-muscle invasive bladder cancer. The efficacy of intravesical chemotherapy is determined by cellular uptake of intravesical drugs. Therefore, drug delivery technologies in the urinary bladder are promising tools for enhancing the efficacy of intravesical chemotherapy. Ultrasound-triggered microbubbles cavitation may enhance the permeability of urothelium and thus may have a potential as a drug delivery technology in the urinary bladder. Meanwhile, the enhanced permeability may increase systemic absorption of intravesical drugs and thus increase adverse effects of drug. The aim of this preliminary safety study was to assess the systemic absorption of an intravesical drug that was delivered by ultrasound-triggered microbubble cavitation in the urinary bladder of normal dogs. Pirarubicin, a derivative of doxorubicin, and ultrasound contrast agent (Sonazoid) microbubbles were administrated in the urinary bladder. Ultrasound (transmitting frequency 5 MHz, pulse duration 0.44 μsec, pulse repetition frequency 7.7 kHz, peak negative pressure -1.2 MPa) was exposed to the bladder using a diagnostic ultrasound probe (PLT-704SBT). The combination of ultrasound and microbubbles did not increase the plasma concentration of intravesical pirarubicin. In addition, hematoxylin and eosin staining showed the combination of ultrasound and microbubble did not cause observable damages of urothelium. The results of this preliminary study demonstrate the safety of the combination of intravesical pirarubicin and ultrasound-triggered microbubble cavitation, i.e., ultrasound-assisted intravesical chemotherapy.